Areas suitable for five leguminous trees and shrubs in Ethiopia: A digital data-based analysis - Berhe, Kahsay; Conchedda, Giulia; Jabbar, M.A. (2001)
Land degradation, low agricultural productivity and poverty are major problems in Ethiopia. The existing resources cannot support the growing human and livestock population. Currently, there is an increasing interest among researchers and development experts in leguminous multipurpose trees and shrubs because these species can address some of these problems. They can be used as a source of supplementary feed and forage for ruminant and non ruminant livestock, green manure, mulch, soil conservation, bee forage, fuel wood, implement and others. The objective of this paper is to define areas suitable for five leguminous trees and shrubs (Calliandra calothyrsus, Sesbania sesban, Leucaena diversifolia, L. pallida and Chamaecytisus palmensis) that were evaluated and found to be promising in some parts of Ethiopia, to other parts of the country, using GIS as a tool. The digital data showed that a large part in the west and south western regions are suitable for C. calothyrsus. Most areas suitable for S. sesban and C. calothyrsus appear to overlaL. pallida was found to be suitable to many parts in the country due to its relatively better drought tolerance. L. diversifolia, on the other hand, could be adapted to only a small area in the country. Large areas of the country extending from north to south and to some highland areas in the east are suitable for C. palmensis. Socioeconomic characteristics are, however, needed before recommending these leguminous trees and shrubs into a farming system